Socialization of the Risk of Excessive Use of Gadgets to Teenagers at SMPN 2 Tarogong Kidul, Jayaraga Village, Tarogong Kidul District, Garut Regency - Gusgus Ghraha Ramdhanie, Gusgus Ghraha Ramdhanie; Bambang Aditya Nugraha, Bambang Aditya Nugraha; Sulastini, Sulastini (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Adolescence is a transitional period from childhood to adulthood characterized by several significant changes in terms of physical, psychological, and social aspects. Adolescence is a period of exploration; they will try many new things. This condition encourages adolescents to engage in risky behavior and unhealthy lifestyles. One of the risks associated with this condition is the excessive use of electronic devices or gadgets. We conducted socialization activities using health promotion and education methods at SMPN 2 Tarogong Kidul, located in Jayaraga Village, Tarogong Kidul District, Garut Regency. The first stage of the activity involves identifying the behavior patterns of students at the school, based on the school's interpretation and perspective. The implementation stage involves the socialization of students at SMPN 2 Tarogong Kidul Garut, utilizing a delivery method that includes lectures, discussions, and questions and answers. During the final stage, we assessed students' understanding through pretests and posttests, which supported the evaluation of their success. Based on the pre-test and post-test completed by the socialization participants, it is evident that the provided material has imparted knowledge to them, demonstrating that students are paying attention to the presented content.